Implications of digital marketing on e-commerce in the context of NRB Bazaar - Asha, Tamanna Reza (BRAC Univeristy, 2018)
This internship report is submitted in a partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2018.